2015
DOI: 10.1038/mi.2014.133
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-targeted vaccination to lung dendritic cells generates tissue-resident memory CD8 T cells that are highly protective against influenza virus infection

Abstract: Influenza virus gains entry into the body by inhalation and initiates its replication cycle within the lung. The early stage of infection, while the virus is confined to the lung mucosa, provides the ideal window of opportunity for an effective immune response to control the infection. Tissue-resident memory (Trm) CD8 T cells, located in a variety of tissues including the lung, are ideally situated to act during this window and stall the infection. The factors involved in the differentiation of lung Trm cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
166
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(182 citation statements)
references
References 33 publications
9
166
1
1
Order By: Relevance
“…In contrast to antigen-independent and local inflammation-driven T RM differentiation in the vagina and salivary gland, local cognate antigen is essential for lung T RM differentiation, 47,64 consistent with the findings that T cells with different TCR specificity elicit distinct T RM forming potential during polyclonal response against influenza virus infection in mice. 67,72,73 Further, TCR signal can induce the expression of anti-viral protein IFITM3 (Interferon Induced Transmembrane Protein 3) in lung T RM cells.…”
Section: Tissue Specific Features Of Trm Cellssupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast to antigen-independent and local inflammation-driven T RM differentiation in the vagina and salivary gland, local cognate antigen is essential for lung T RM differentiation, 47,64 consistent with the findings that T cells with different TCR specificity elicit distinct T RM forming potential during polyclonal response against influenza virus infection in mice. 67,72,73 Further, TCR signal can induce the expression of anti-viral protein IFITM3 (Interferon Induced Transmembrane Protein 3) in lung T RM cells.…”
Section: Tissue Specific Features Of Trm Cellssupporting
confidence: 85%
“…The differentiation of CD103 + lung T RM cells is TGF-β-dependent 64,68 and requires CD4-help and cross-Priming signals from DNGR-1 + DCs during the initial priming phase. 37,42 4–1BB signal to T cells is critical for the formation of lung T RM cells in a competitive setting.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%
“…injection preferentially induces serum Ab response but fails to control either one (18). Targeting lung dendritic cells (DCs) via intranasal vaccination with Ag coupled to mAbs against endocytic receptors on DCs induces lung T RM CD8 + T cells that protect against lethal influenza challenge (19). Collectively, these data suggest that site of vaccine Ag priming could influence the localization of T RM cells which are crucial for local host defense.…”
mentioning
confidence: 96%
“…As Trm cell development within the lung is heavily influenced by local antigen recognition (9,20), the relative epitope abundance within the lung over the course of an influenza virus infection likely modulates the immunodominance hierarchy within the Trm cell compartment, the relative epitope abundance within the lung over the course of an influenza virus infection likely modulates the Processing of peripheral blood and human tissues. PBMCs were isolated by Ficoll-Paque density-gradient centrifugation and cryopreserved.…”
Section: Cd69mentioning
confidence: 99%
“…Memory CD8 + T cells can be broadly divided into 3 subsets: 2 highly mobile circulating memory CD8 + T cell subsets, termed central and effector memory T cells (Tem cells), and a sessile memory T cell pool that is resident within peripheral tissues. While it was unclear from these clinical studies which memory T cell subset was responsible for the observed protection, growing evidence from animal models shows that not all memory CD8 + T cell subsets are equally protective against influenza virus infection, with only the tissue resident memory (Trm) subset being absolutely indispensable for crossprotection against different strains of influenza virus (8,9).…”
Section: Introductionmentioning
confidence: 99%